TUMBUHAN YANG ADA DI AL-QURAN SEBAGAI EKSPRESI DALAM SENI RELIEF KAYU - Ardi Rahmad; Ahmad Akmal; Febri Yulika (Gorga : Jurnal Seni Rupa, 2022)
Al-Quran is the holy book of Muslims, some of its verses explain stories related to plants. The Qur'an mentions plants as a parable to reveal a truth and describe the physical form and its benefits for human life. The diversity of plants in the Qur'an has wisdom and purpose for human life, such as some of the stories written in the Qur'an, some are sworn in by Allah, some are used as parables, some are used as a source of life for humans. This relief artwork uses the concept of reinterpretation by changing the plant phenomena in the Al-Quran into creative stimuli, namely wood relief art such as Tin, Olive and Pumpkin. In general, relief can be defined as a 2D artwork of art created by sculpting the part of the medium that will be removed to create the desired shape. The purpose of the creation of this relief artwork is to express the literacy of Al-Quran verses about plants into wood relief art to bring out the wisdom and phenomena of plants in the Al-Quran. The creation of plant reliefs in the Al-Quran uses the Eksperimen, Contemplation, Formation and Manifestation methods. The artwork created presents a form that is related to the story and its existence in the Al-Quran so as to provide information related to the plants in the Al-Quran with aesthetic value and visual epistemology. Expressions that present information and plant phenomena in the Qur'an can be enjoyed visually, including three artworks of wood relief art with carving techniques entitled Yaqtin, Middle and At-Tiin.Keywords: plants, Al-Quran, expressions, wood relief. AbstrakPenciptaan relief tumbuhan yang ada di dalam Al-Quran terinspirasi dari penyebutan dan fenomena tumbuh-tumbuhan yang ada di dalamnya. Kisah tentang tumbuhan yang dituangkan dalam bentuk karya relief kayu sangat jarang ditemukan. Karya seni relief ini menggunakan konsep reinterpretasi dengan cara mengubah fenomena tentang tumbuhan yang menjadi rangsang cipta karya seni yaitu seni relief kayu seperti tumbuhan tin, zaitun, dan labu. Secara umum relief dapat diartikan sebagai karya seni dua dimensi (2D) yang diciptakan dengan teknik memahat. Tujuan penciptaan karya relief ini adalah mengekspresikan ayat Al-Quran tentang tumbuhan menjadi seni relief kayu untuk memunculkan hikmah dan fenomena tumbuhan yang ada di dalam Al-Quran. Penciptaan relief tumbuhan yang ada di dalam Al-Quran menggunakan metode eksperimen, perenungan, pembentukan, dan perwujudan. Karya yang diciptakan menghadirkan bentuk yang berhubungan dengan kisah dan keberadaannya di dalam Al-Quran sehingga memberikan informasi yang berhubungan dengan tumbuhan yang ada di dalam Al-Quran dengan nilai estetik dan epistemologi visual. Ekspresi yang menghadirkan informasi dan fenomena tumbuhan yang ada di dalam Al-Quran dapat dinikmati secara visual di antaranya adalah tiga buah karya seni relief kayu dengan teknik ukir yang berjudul Yaqtin, Pertengahan dan At-Tin.Kata Kunci: tumbuhan, Al-Quran, ekspresi, relief kayu. Authors: Ardi Rahmad: Institut Seni Indonesia PadangpanjangAhmad Akmal: Institut Seni Indonesia PadangpanjangFebri Yulika : Institut Seni Indonesia PadangpanjangReferences: Al-Qur’an dan terjemahannya. (2008). Departemen Agama RI. Bandung: Diponegoro.Amrullah, Abdul, Malik, Karim. (1983). Tafsir Al-Azhar. Jakarta: Gema Insani.Junaidi, Deni. (2017). Estetika, Jalinan Subjek Objek dan Nilai. Yogyakarta. ArtCiv.Kartika, Dharsono Sony. (2016). Kreasi Artistik. Karanganyar. Surakarta: UNS.Sahman, H. (1992). Mengenali Dunia Seni Rupa. Semarang: IKIP Semarang Press.Salam, Sofyan. (2020). Pengetahuan Dasar Seni Rupa. . Makassar: Badan Penerbit UNM.Susanto, M. (2002). Diksi Rupa. Yogyakarta: Kanisius.